PERSEPSI MASYARAKAT TERHADAP WISATAWAN DI CANDI MUARA TAKUS KABUPATEN KAMPAR - Habir Jais; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Attractions Muara Takus as a relic of Buddhist temple located in the area throughout the Moslem inhabitant, and still stronger hold their customs and culture. This temple began much visited by tourists from various ethnic backgrounds, religions and cultures. This certainly raises different perceptions against the travelers.This study aims to determine the public perception of the tourists visiting Muara Takus Kampar regency. This perception viewed from the aspect of cognitive, affective and conative aspect.The method used is qualitative method. In a study that is the subject of research amounted to 7 people, which is the surrounding community as informants. To determine the informant researchers used purposive sampling technique, which the researchers took the informant based on certain criteria which are based on objective research.This study identified into three main issues, namely the perception viewed from the aspect of cognitive, affective and conative aspect. Thus researchers can determine how the public perception of the tourists in Kampar regency Muara Takus.Keywords: Perception, Society, Travelers, Muara Takus.